Study of journal bearing on a rolling piston compressor - Chua, Si Yun (2015)
This project explores a method for evaluating significant design parameters of a journal bearing, which includes the load capacity, maximum pressure, power loss, minimum oil film thickness, oil flow and maximum temperature in the oil film. Journal bearings are widely used in rotating systems due to its good damping and low wear characteristics. It must be able to support the required load with slow wear rate and minimum energy loss. Journal bearings work on the principle of hydrodynamic lubrication to cause a pressure build-up, pushing surfaces apart to prevent metal to metal contact. Hydrodynamic flow is a function of the bearing dimensions, geometry, eccentricity, clearance and rotational speed. A mathematical model is used to model the design parameters of a journal bearing. By formulating the mathematical model into a computer program, employing the FORTRAN programming language, a parametric study is carried out to investigate how changing certain parameters can have on the performance of a journal bearing. The varying parameters studied one at a time are the rotational speed of the shaft, the shaft diameter, the bearing length, the load capacity of a bearing and its eccentricity. Performances of the bearings to be evaluated against the varying parameters are the maximum pressure and temperature, and the minimum oil film thickness.